Analisis dan Penilaian Kinerja Portofolio Optimal Saham-Saham LQ-45 - eko, umanto (UI Scholars Hub, 2010)
Portfolio is basically related to how one allocates a number of stocks into various investment types that results on optimal profits. By making diversification, investor may reduce the rate of risk and at the same time optimize the rate of expected return. Based on that, this research raises the problem of how to design an optimal portfolio simulation, i.e. a combination of liquid shares LQ 45 listed in Jakarta Stock Exchange (Now is known as Indonesia Stock Exchange, after the merger with Surabaya Stock Exchange) in the period of 2002- 2007 by using Single Index Model and Constant Correlation Model. Single Index Model is a model of portfolio analysis using the account of Excess Return to Beta (ERB) Ratio and value of C* to gain optimal shares on portfolio. The procedure of Constant Correlation Model is exactly parallel to the case of Single Index Model. However, unlike in the Single Index Model, all securities are ranked by Excess Return to Standard Deviation (ERS) instead of Excess Return to Risk. After securities are ranked using the above ratio, securities with greater Excess Return to Standard Deviation and Cut off Point (C*) are included into the optimal portfolio.